Health-seeking Behavior of People in Twin Cities of Pakistan during the COVID-19 Pandemic: A Cross-Sectional Study - Yamin, Tayyaba; Khaliq, Fatima; Khalid, Afaq; Ihtisham, Ramish (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Background: The pandemic presents a novel area for research, and making use of this opportunity makes this study crucial for assessing trends in health-seeking behavior during this period. The findings are significant for authorities, as they can inform policy development aimed at improving public health responses. Specifically, the study focuses on examining the general public's response to health-related issues during the pandemic, exploring reasons for avoiding medical consultations, assessing the prevalence of self-medication, and analyzing the relationship between self-medication and socio-demographic variables. Objectives: This study is focused on determining the response of the general public to health-related issues during the coronavirus pandemic, evaluating the reasons for avoiding medical consultation, assessing the frequency of self-medication, and finding the relation of self-medication with socio-demographic variables. Material and methods: A self-developed questionnaire was used, and data collection was conducted online through Google Forms. Data entry and analysis were performed using SPSS 25.0 software. Categorical data such as gender, socioeconomic status, education level, and self-medication practices were presented as frequencies and percentages. The chi-square test was employed to determine the correlation between self-medication practices and categorical factors like gender, age, socioeconomic status, and education level, with a p-value of less than 0.05 considered statistically significant. Results: Most respondents did not consult doctors about their symptoms and instead resorted to self-medication. Many participants also used telemedicine during this duration due to fear of getting infected by COVID-19. A significant positive association was found between self-medication practice with age, socioeconomic status, and education. Conclusion: This study highlighted that patients were resistant to visiting hospitals during a pandemic. Government healthcare providers should ensure that patients feel comfortable while going to hospitals and should arrange some campaigns to spread awareness about the adverse effects of using self-medication.